2022
DOI: 10.1109/jbhi.2022.3193365
|View full text |Cite
|
Sign up to set email alerts
|

Reliably Filter Drug-Induced Liver Injury Literature With Natural Language Processing and Conformal Prediction

Abstract: Drug-induced liver injury describes the adverse effects of drugs that damage liver. Life-threatening results including liver failure or death were also reported in severe cases. Therefore, the events related to liver injury are strictly monitored for all approved drugs and the liver toxicity is an important assessments for new drug candidates. These reports are documented in research papers that contain preliminary in vitro and in vivo experiments. Conventionally, data extraction from previous publications rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The Critical Assessment of Massive Data Analysis (CAMDA) 2022 in collaboration with the Intelligent Systems for Molecular Biology (ISMB) hosted the Literature AI for Drug Induced Liver Injury (DILI) challenge [1]. A curated dataset, consisting of 277,016 DILI annotated papers, was downloaded from the CAMDA website.…”
mentioning
confidence: 99%
“…The Critical Assessment of Massive Data Analysis (CAMDA) 2022 in collaboration with the Intelligent Systems for Molecular Biology (ISMB) hosted the Literature AI for Drug Induced Liver Injury (DILI) challenge [1]. A curated dataset, consisting of 277,016 DILI annotated papers, was downloaded from the CAMDA website.…”
mentioning
confidence: 99%
“…242 The model using TF-IDF and logistic regression achieved an accuracy of 0.957 with an ensemble model fine-tuned to lower false-negative cases, achieving an accuracy of 0.954 and an F1 score of 0.955. 242 The ensemble model identified important words in positive/negative predictions, providing researchers with a rapid filter for DILI-related literature. Overall, these research studies aim to assist regulatory activities in evaluating drug safety and identifying potential DILI risks, making it indirectly related to active drug toxicity prediction efforts.…”
Section: Normalizing Flow and Diffusionmentioning
confidence: 99%
“…The study demonstrated that the model could capture the semantic meanings of complex text in drug labeling and was portable across agencies, indicating the potential for using AI technologies to modernize and advance regulatory science. Another similar study used BERT-powered NLP to automatically filter out DILI literature from around 28,000 papers provided by the CAMDA challenge . The model using TF-IDF and logistic regression achieved an accuracy of 0.957 with an ensemble model fine-tuned to lower false-negative cases, achieving an accuracy of 0.954 and an F1 score of 0.955 .…”
Section: Deep Learning In Predictive Drug Toxicity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our current DILI study, binary classification has been considered. Logistic regression is exemplified for DILI classification [18,19]. Once again, if 𝑥 be the input features of dimension 𝑛, and 𝑦 be the binary class with class labels 0 and 1.…”
Section: Model Selection and Mathematical Analysismentioning
confidence: 99%